Angiographic performance of everolimus‐eluting stents for the treatment of coronary in‐stent restenosis in daily practice. Issue 5 (26th August 2020) - Wiebe, Jens; Rai, Himanshu; Kuna, Constantin; Cassese, Salvatore; Kessler, Thorsten; Rheude, Tobias; Colleran, Roisin; Schunkert, Heribert; Koch, Tobias; Kufner, Sebastian; Joner, Michael; Kastrati, Adnan; et al.
Abstract: Objectives: The present study aims to analyze the angiographic anti‐restenotic performance of durable polymer everolimus‐eluting stents (EES) for the treatment of in‐stent restenosis (ISR) in daily practice. Background: Randomized data is available supporting the use of drug‐coated balloons and drug‐eluting stents for the treatment of ISR; however, additional real‐world data including angiographic follow‐up is needed. Methods: Patients who underwent EES‐implantation for the treatment of drug‐eluting stent ISR and attended for a 6–8 months angiographic surveillance were analyzed. Off‐line assessment of the angiograms was conducted at a central quantitative coronary angiographic core laboratory. Results: A total of 426 patients with ISR were treated with EES and had undergone angiographic follow‐up. The mean age was 66.8 ± 9.9 years and 27.5% suffered from diabetes. A total of 459 lesions were treated. The diameter stenosis decreased from 64.3 ± 19.1% (preprocedural) to 12.0 ± 6.4% (postprocedural). At 6–8 months angiographic follow‐up, the in‐segment diameter stenosis was 38.3 ± 21.7% and the in‐stent late luminal loss was 0.54 ± 0.74 mm in the treated area analysis. The rate of recurrent binary restenosis was 25.7%. Conclusions: In the setting of ISR, the angiographic anti‐restenotic efficacy of stenting with EES is comparable to that observed in randomized clinical trials and less favorable than its performance in patients undergoing stenting for de novo disease.